Efficacy and Safety of Intraoperative Lumbar Drain in Endoscopic Skull Base Tumor Resection: A Meta-Analysis - Guo, Xiaoming; Zhu, Yueli; Hong, Yuan (Frontiers in Oncology, 2020)
Objectives: This study aims to evaluate the efficacy and safety of lumbar drainage (LD) in preventing cerebrospinal fluid (CSF) leaks after endoscopic skull base tumor resection. Methods: A systematic online search was conducted using PubMed, Embase, Scopus, Web of Science, and Cochrane Library from January 2006 to July 2019. Data analyses were performed by the Cochrane Collaboration’s Review Manager 5.3 software. Results: Eight studies, including two randomized controlled trials and six observational studies, met the inclusion criteria. No significant difference was found in the postoperative CSF leak rate between LD group and the non-LD group (OR 0.80, 95%CI 0.37 - 1.74, I2 = 37%, P = 0.57). Subgroup analysis of the intraoperative high-flow leaks, including 4 studies and 313 patients, showed that LD was associated with reduced likelihood of postoperative CSF leak (OR 0.37, 95%CI 0.17 - 0.83, I2 = 0%, P = 0.02). The placement of LD was related to increased risk of headache compared with non-LD use and no significant difference was found in the occurrence of deep vein thromboses and pulmonary emboli between two groups. Conclusion: LD is not recommended in all patients undergoing endoscopic skull base tumor resection. But for patients with intraoperative high-flow leaks, LD is effective and safe in reducing risk of CSF leak.